The impact of corporate governance on voluntary disclosure among pulic-listed companies in Malaysia / Mohd Rashdan Sallehuddin - Sallehuddin, Mohd Rashdan (2016)
This paper examines the relationships of corporate governance characteristics and ownership with the level of voluntary disclosures in the annual reports of the 254 public-listed firms in Bursa Malaysia for the year 2010. Regression analysis was used to examine the relationship between firms' voluntary disclosure and independent variables consisting of board's size, board's independence, audit committee size and managerial ownership. The study revealed that only board's independence has a significant relationship with firms' voluntary disclosure. In contrast, the extent of corporate voluntary disclosure is insignificant with regard to board's size, audit committee size and managerial ownership. This study provides evidence for regulatory bodies such as Bursa Malaysia and Securities Commission Malaysia to look further and enhancing the corporate governance framework in order to grasp the benefits behind the enactment of corporate governance in Malaysia.